IMPLEMENTATION OF PROFESSIONAL ZAKAT BASED ON THE REGIONAL REGULATION OF PALEMBANG CITY NUMBER 4 OF 2017 AT THE PALEMBANG CITY GOVERNMENT OFFICE - Tamudin, M.; Fitriyati, Yusida (Nurani, 2021)
This paper examines the implementation of professional zakat based on the regional regulation of the city of Palembang Number 4 of 2017 concerning zakat management at the Palembang city government office.This research is a field research by conducting a study of the laws that apply in society. This study looks at the application of professional zakat based on the Regional Regulation of Palembang City Number 4 of 2017 at the Palembang City Government Office. There are 3 problem formulations in this study, including "1. How is the implementation of professional zakat based on the Regional Regulation of Palembang City Number 4 of 2017 at the Palembang City Government Office? 2. What are the factors that influence the implementation of professional zakat based on the Regional Regulation of Palembang City Number 4 of 2017 at the Palembang City Government Office? 3. What are the efforts made by the Palembang City Government in overcoming the problem of implementing professional zakat based on the Palembang City Regional Regulation Number 4 of 2017? From the results of the study it can be concluded that the implementation of professional zakat based on the regional city regulation of Palembang number 4 of 2017 in the Palembang city government office has been carried out but has not been maximized. There are still many ASNs (civilApparatus) who have not deposited professional zakat to the Palembang City BAZNAS. His awareness of paying professional zakat has only reached 13% of the existing muzakki. The enforcement of administrative sanctions or fines has also not been implemented due to political reasons. The factors that influence the implementation of professional zakat in the Palembang city government office are: the rule of law factor, the Palembang City BAZNAS factor, Keywords :Implementation, regional regulations, professional zakat.